Pendidikan Spiritual Berbasis Tasawuf (Upaya Meminimalisir Perilaku Menyimpang Homoseksual di Pesantren) - Azzam Syukur Rahmatullah; Muhammad Azhar (Cendekia: Kependidikan dan Kemasyarakatan, 2019)
Abstract: This research is a type of field research in two old Pesantren “Salafiyah and Khalafiyah.” The two pesantren in question are Pesantren Kyai Kholil Bangkalan and Al-Hikam Bangkalan Madura. While the analiysis  uses studies namely reseacrh is in-depth discusson of the contents of written information. The result of this study indicate that the motivation of sufism-based spiritual education in Pesantren Salafiyah Al Kholiliyah are:First, guarding motivation from homosexual tyranny, Second, motivation worship behavior so that the spiritual strength of the santri, Third, behavioral motivation to change positively. While the motivation of sufism based spiritual education in Pesantren al-Hikam Bangkalan Madura, are : First, santri have high spiritual feelingsso that they can fortify themselves from homosexual behavior, seconds, the students are not only intelligent in cognitive aspects but also intelligent in the spiritual fiel.Thirds,  as a medium for minimizing public ills, which in this case is homosexual. As for the contents of sufism-based spiritual education as an effort to minimize the behavior of homosexual students are; First, Talqin stage, namely the stage of awareness of student, second, stages of remembrance that is the stage of cleansing the heart. Third, the  night bathing stage and the next stage are reward and punishment stages, and the last stage is the stage of group life. While the contents of sufismbased spiritual education in Pesantren al-Hikam there are several formulas; First, taubatan nasuha, second, zuhud, thirds, wara’, fourth, tawakal, fifth, mahabbah sixth, makrifat.  ملخص: سًمِيَ هَذَا الْبَحْثُ بِالْبَحْثِ الْمَيْدَانِ, حَيْثُ جَمَعَ الْكَاتِبُ الحَقَائِقَ فِي الْمَعْهَدَيْنِ. هُمَا مَعْهَدُ كِيَاهِي خَلِيْل السَلَفِي وَ مَعْهَدُ الْحِكَم الخَلَفِي فِي مَدِيْنَةِ مَادُوْرَا. وَبَعْدَ اَنْ جَمَعَ الْحَقَائِقَ. قَامَ الْكَاتِبُ بِتَحْلِيْلِهَا مُسْتَخْدِمًا الطَّرِيْقَةُ الْوَصْفِيَةُ يَعْنِي يَبْحَثُ عَنِ الْمَصَادِرِ الْمَكْتُوْبَةِ فِي الْمَعْهَدِ. وَاَمَّا الإِقْتِرَابُ الْمُسْتَعْمَلُ هُوَ إِقْتِرَابُ الْمُقَارَنَةِ, لِأَنَّ الْكَاتِبَ يُرِيْدُ اَنْ يُقَارِنَ التَّصَوُّفَ بَيْنَ الْمَعْهَدَيْنِ. وَأَعْرَاضُ الْبَحْثِ وَمَنَافِعُهُ 1) الْمُحَافَظَةُ عَنِ الزِّنَا 2) تَشْجِيْعُ عِبَادَةِ الْعَامِلِ 3) تَشْجِيْعُ الطَالِبِ اِلَي الْخَيْرِ. وَاَمَّا التَّشْجِيْعُ التَّرْبِيَةِ التَّصَوُّفِيَّةِ فِي الْمَعْهَدِ الْحِكَمْ 1) التَرْبِيَةُ الرُّوْحِيَّةُ للطُّلاَبِ 2) لِلطُّلاَبِ لَهُمْ اَفْكَارٌ وَرُوْحِيَّةٌ 3) الوَسِيْلَةُ وَالإِعْلاَم لِتَقْلِيْلِ الزِنَا. وَاَمَّا تَشْجيْعُ التَّرْبِيَةِ التَّصَوُّفِيَّةِ فِي مَعْهَدِ كِيَاهي خَلِيْل 1)التَلْقِيْنُ وَهُوَ الوَعْيُ عَنِ النَّفْسِ 2) الذِّكْرُ لِتَطْهِيْرِ الْقَلْبِ 3) الإِسْتِحْمَامُ فِي اللَّيْلِ 4) الوَعْدُ وَالوَعِيْدُ 5) الحَيَاةُ الإِجْتِمَاعِيَّةُ/ العَيْشُ الإِجْتِمَاعِي.  وَاَمَّاالتَّرْبِيَةُ التَّصَوُّفِيَّةُ فِي مَعْهَدِ الْحِكَم 1) التَّوْبَةُ 2) الزُّهْدُ 3) الوَرَعُ 4) التَّوَكُّلُ 5)المَحَبَّةُ 6) المَعْرِفَةُ